ANALISIS SPEKTRUM DATA GAYABERAT GGMPLUS DAERAH WAYRATAI, LAMPUNG - Syamsurijal Rasimeng; Ilham Dani; Widya Putri Syahranti; Ivana Jayarani Sitompul; Fadhil Muhammad Nizam (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2024)
The weight force method is a geophysical method that is sensitive to vertical changes, therefore this method is favored for studying intrusion contacts, bedrock, geological structures, ancient river deposits, holes in the rock mass, buried shaff, and others. The location of the research area is in the Way Ratai geothermal area, Padang Cermin District, Pesawaran Regency, Lampung Province. This research aims to determine the depth of regional and residual anomalies and to identify weight force anomalies based on 2-dimensional subsurface conditions. Five passes were sliced, namely A-A', B-B', C-C', D-D', and E-E' on the complete Bouguer anomaly cross section, and the resulting values of regional depth, residual, wavelength, and cutoff value as the boundary of the intersection between regional and residual anomalies. The complete Bouguer anomaly values range from 54 mGal to 100 mGal, the regional anomaly is 56 mGal to 90 mGal, and the residual anomaly is 19 mGal to 4 mGal. The depth of the regional anomaly is 5219.4m and the residual anomaly is at a depth of 336.77m.